2014
DOI: 10.5194/acp-14-4875-2014
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial characteristics of ozone depletion events from measurements in the Arctic

Abstract: Abstract. Following polar sunrise in the Arctic springtime, tropospheric ozone episodically decreases rapidly to near-zero levels during ozone depletion events (ODEs). Many uncertainties remain in our understanding of ODE characteristics, including the temporal and spatial scales, as well as environmental drivers. Measurements of ozone, bromine monoxide (BrO), and meteorology were obtained during several deployments of autonomous, ice-tethered buoys (O-Buoys) from both coastal sites and over the Arctic Ocean; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
61
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 93 publications
10
61
0
3
Order By: Relevance
“…Based on these results, it can be concluded that iodine has the potential to have a much greater impact on ozone depletion than chlorine. The combination of Br, Cl and low iodine, resulting in an 8.5 h depletion timescale, is consistent with the fast-end timescales observed over the Beaufort Sea by Halfacre et al (2014).…”
Section: Atmossupporting
confidence: 69%
See 3 more Smart Citations
“…Based on these results, it can be concluded that iodine has the potential to have a much greater impact on ozone depletion than chlorine. The combination of Br, Cl and low iodine, resulting in an 8.5 h depletion timescale, is consistent with the fast-end timescales observed over the Beaufort Sea by Halfacre et al (2014).…”
Section: Atmossupporting
confidence: 69%
“…Backtrajectories for periods of very high [Cl 2 ] during OASIS indicate air mass transport over the surface of the Arctic Ocean . Ozone instruments onboard the OBuoy network of sea ice-tethered buoys (Knepp et al, 2010) in the Arctic Ocean have also indicated very fast ozone depletions, with a median timescale of 10.4 h and numerous individual events much faster than that (Halfacre et al, 2014). Unfortunately, we are limited by a lack of Cl 2 measurements from across the frozen Arctic Ocean, and, thus, it is not possible to speculate how widespread this elevated Cl 2 may be.…”
Section: Atmosmentioning
confidence: 96%
See 2 more Smart Citations
“…In order to investigate the hinted heterogeneity of the Antarctic lower troposphere regarding reactive bromine (BrOx = Br + BrO), in this section the budget of bromine [Br] is estimated considering steady state of BrO in a pristine atmosphere with virtually no NO (e.g., Zeng at al., 2006) and a concentration of ClO, HO2 and OH of 1.7·10 8 molec cm -3 , 2.2·10 7 molec cm -3 20 and 3.9·10 5 molec cm -3 , respectively (e.g., Halfacre et al, 2014;Bloss et al, 2007). Hence, [Br] can be estimated from the observed BrO and O3 concentrations as (e.g., Hausmann and Platt, 1994;Le Bras and Platt, 1995;Zeng et al, 2006;Stephens et al, 2012):…”
Section: Brox In Antarcticamentioning
confidence: 99%